Principal Leadership as a Supporting Factor for Teacher Performance in the Implementation of the Independent Curriculum at SMP Negeri Unggul Sigli - Ismawati, Nurliza; Bahrun, Bahrun; Niswanto, Niswanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the role of principal leadership in supporting the performance of Driving Teachers in implementing the Independent Curriculum at SMP Negeri Unggul Sigli. Using a qualitative case study approach, data were collected through interviews, observations, and documentation involving principals, Driving Teachers, non-Driving Teachers, and students. The findings reveal that principals adopt a transformational leadership style by providing motivation, mentoring, and learning facilities, enhancing teacher performance in project-based learning, collaboration, and technology use. Principals also foster a collaborative school culture, strengthening curriculum implementation. Challenges include limited understanding among non-Driving Teachers, time constraints, and budget limitations. The study highlights the need for training, resource optimization, and effective leadership to ensure sustainable curriculum implementation.